Cognitive Impairment in Late-Life Depression: A Comparative Study of Healthy Older People, Late-Life Depression, and Mild Alzheimer's Disease Using Multivariate Base Rates of Low Scores - Masse, Caroline; Vandel, Pierre; Sylvestre, Géraldine; Noiret, Nicolas; Bennabi, Djamila; Mauny, Frédéric; Puyraveau, Marc; Barsznica, Yoan; Dartevelle, Jonathan; Meyer, Agatha; Binetruy, Mickaël; Lavaux, Marie; et al. (Frontiers in Psychology, 2021)
Late-Life Depression (LLD) is often associated with cognitive impairment. However, distinction between cognitive impairment due to LLD and those due to normal aging or mild Alzheimer Disease (AD) remain difficult. The aim of this study was to present and compare the multivariate base rates of low scores in LLD, mild AD and healthy control groups on a battery of neuropsychological tests. Participants (ages 60-89) were 352 older healthy adults, 390 patients with LLD and 234 patients with mild AD (i.e. MMSE ≥ 20). Multivariate base rates of low scores (i.e. ≤ 5th percentile) were calculated for each participant group within different cognitive domains (verbal episodic memory, executive skills, mental processing speed, constructional praxis, and language/semantic memory). Obtaining at least one low score was relatively common in healthy elderly controls (from 9.4% to 17.6%), and may thus result in a large number of false positives. By contrast, having at least two low scores was unusual (from 0.3% to 4.6%) and seems to be a more reliable criterion for identifying cognitive impairment in LLD. Having at least three low memory scores was poorly associated with LLD (5.9%) compared to mild AD (76.1%) and may provide a useful way to differentiate between these two conditions (χ2 (1) = 329.8, p < 0.001; Odds Ratio = 50.7, 95% CI = 38.2-77.5). The multivariate base rate information about low scores in healthy elderly and mild AD may help clinicians to identify cognitive impairments in LLD patients, improve the clinical decision-making, and target those who require regular cognitive and clinical follow-up.